Study and Analysis on The Planning of The Maintenance of The Architectural Public Work, Built in The City of Azogues, Province of Cañar – Ecuador - Vargas, María Viviana Saquicela; Alvear, Boris Orellana (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2023)
The useful life of a work is conceived from the exploitation of resources for the generation of materials, design, construction, use and operation, deterioration or demolition and, possibly, the recycling of elements; reason why at present arises the inherent need to plan the maintenance and conservation of works, especially those destined for public uipamiento, granting a longer time of service to the urban-architectural public works, built by public entities in the city of Azogues, thus providing a Greater sustainability, with a correct execution and maintenance plan, rational use of materials at the time of construction and longer service time; which reduce long-term work costs, avoiding deterioration, which is sometimes irreversible and implies a high expense in repairs or, the low of said works.